Pembangunan Kamar Mandi Untuk Masjid Baitussalam Sebagai Upaya Peningkatan Kualitas Kesehatan dan Sanitasi - Hidayati, Noor; Widiyatmoko; Ekayuliana, Arifia; Syuriadi, Adi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2023)
Baitussalam Mosque is located in the Kalibaru scenic housing estate, Kalibaru Village, Cilodong, Depok city of West Java Province. It was built in 2006 by the help of the red crescent body. In addition to being a place of worship, the Baitusaalm mosque actively carries out humanitarian activities such as free medical treatment, mass circumcision, donations for orphans, qur’anic recital and memorization (tahfiz) houses, and other activities. However, since its inception, the Baitussalam Mosque still does not have its own bathroom for male worshipers. Henceforth, the congregation is diverted to the bathroom of tahfidz's house. Meanwhile, the tahfidz house is still in the process of being renovated. Therefore, the Power Generation Study Program, Mechanical Engineering Department, Jakarta State Polytechnic wants to assist the mosque member in constructing the required facilities and infrastructure. The target of the service is to help build bathroom infrastructure for the mosque in order to improve the health and sanitation of the Baitussalam mosque congregation. The method begins with discussions with mosque administrators, site surveys, making bathroom designs as needed, and then the process of building Baitussalam Mosque toilets. The result of this community development activity is the completion construction of the bathroom which is followed by a small survey that denoted the satisfaction of the administrators and worshipers of the mosque. Masjid Baitussalam, merupakan masjid yang berada di perumahan Kalibaru Permai Kelurahan Kalibaru, Cilodong, Depok. Masjid ini dibangun pada tahun 2006 oleh bantuan dari red crescent. Selain menjadi tempat ibadah masjid Baitusaalm aktif melakukan kegiatan kemanusiaan seperti pengobatan gratis, khitanaan massal, santunan anak yatim, rumah tahfiz serta kegiatan lainnya. Namun dari tahun 2006 hingga kini, Masjid Baitussalam masih belum memiliki kamar mandi untuk jamaah pria, sehingga jamaah akan dialihkan ke kamar mandi rumah tahfidz. Masalahnya, rumah tahfidz juga masih terus dalam proses pembangunan menggunakan dana donatur. Target pengabdi adalah membantu pembanguan prasarana kamar mandi untuk masjid Baitussalam, dalam rangka meningkatkan Kesehatan dan sanitasi jamaah masjid Baitussalam. Adapun metode pelaksanaan diawali dengan diskusi bersama pengurus masjid, survey lokasi, pembuatan design kamar mandi sesuai kebutuhan, dilanjutkan dengan proses pembangunan toilet Masjid Baitussalam. Hasil kegiatan ini adalah pembangunan kamar mandi yang ditandai dengan kepuasan dari pengurus serta jamaah Masjid Baitussalam menggunakan skala likert.